Encyclopedia of statistical sciences : Vol. 4, Icing................. - Wiley InterScience (Online service) (New York : John Wiley, 2005)
Reference tool covering statistics, probability theory, biostatistics, quality control, and economics with emphasis in applications of statistical methods in sociology, engineering, computer science, biomedicine, psychology, survey methodology, and other client disciplines. This 2nd edition collects the entire original edition, plus supplements and updates.
Includes bibliographical references and index.
Issued also in print.
Mode of access: World Wide Web.
Keywords: Statistics -- Encyclopedias; Electronic reference sources